ADUBAÇÃO DE SOQUEIRA DE CANA-DE-AÇUCAR COM CARBONATO/BICARBONATO DE AMÔNIO - Bernardi, Alberto C. de Campos; Oliveira, Fábio A. de; Bittencourt, Valdomiro de C.; Carmello, Quirino A. de C. (REVISTA DE AGRICULTURA, 2015)
ADUBAÇÃO DE SOQUEIRA DE CANA-DE-AÇUCAR COM CARBONATO/BICARBONATO DE AMÔNIO